Loganin possesses neuroprotective properties, restores SMN protein and activates protein synthesis positive regulator Akt/mTOR in experimental models of spinal muscular atrophy. (September 2016) - Tseng, Yu-Ting; Chen, Cheng-Sheng; Jong, Yuh-Jyh; Chang, Fang-Rong; Lo, Yi-Ching
Graphical abstract: Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive neurodegenerative disease characterized by motor neurons degeneration and muscular atrophy. There is no effective SMA treatment. Loganin is a botanical candidate with anti-inflammatory, anti-oxidant, glucose-lowering and anti-diabetic nephropathy activities. The aim of this study is to investigate the potential protective effects of loganin on SMA using two cellular models, SMN-deficient NSC34 cells and SMA patient fibroblasts, and an animal disease model, SMAο7 mice. In SMN-deficient NSC34 cells, loganin increased cell viability, neurite length, and expressions of SMN, Gemin2, SMN-Gemin2 complex, p-Akt, p-GSK-3β, p-CREB, BDNF and Bcl-2. However, both AG1024 (IGF-1 R antagonist) and IGF-1 R siRNA attenuated the protective effects of loganin on SMN level and cell viability in SMN-deficient NSC34 cells. In SMA patient fibroblasts, loganin up-regulated levels of SMN, FL-SMN2, and Gemins, increased numbers of SMN-containing nuclear gems, modulated splicing factors, and up-regulated p-Akt. Furthermore, in the brain, spinal cord and gastrocnemius muscle of SMAο7 mice, loganin up-regulated the expressions of SMN and p-Akt. Results from righting reflex and hind-limb suspension tests indicated loganin improved muscle strength of SMAο7 mice; moreover, loganin activated Akt/mTOR signal and inhibited atrogin-1/MuRF-1 signal in gastrocnemius muscle of SMAο7 mice. Loganin also increased body weight, but the average lifespan of loganin (20 mg/kg/day)-treated SMA mice was 16.80 ± 0.73 days, while saline-treated SMA mice was 10.91 ± 0.96 days. In conclusion, the present results demonstrate that loganin provides benefits to SMA therapeutics via improving SMN restoration, muscle strength and body weight. IGF-1 plays an important role in loganin neuroprotection. Loganin can be therefore a valuable complementary candidate for treatment of neuromuscular diseases via regulation of muscle protein synthesis and neuroprotection.